The links between the Buen Vivir and Decolonial Feminism: An approach drawn from experiences in Bolivia and Ecuador - Dennis Lucy Avilés Irahola; Eva Shamiran Youkhana (University of Bonn, Center for Development Research (ZEF), 2024)
The different theoretical constructions around the conceptualizations of Buen Vivir and decolonial feminisms have been the subject of fervent debate at the beginning of the governmental periods of Evo Morales in Bolivia (2006 - 2019) and Rafael Correa in Ecuador (2007 - 2017) when Constitutional Assemblies were installed to develop and approve the new Bolivian and Ecuadorian Constitutions. The Assemblies framed unprecedented dialogues of women's and feminists' movements with other political and social actors who, like them, wanted to see changes in the deeply colonial histories of their countries. This article analyses the way the Buen Vivir was translated to specific discourses depending on whether it was presented as an indigenous, modern or postmodern proposal and how these translations addressed (or not) women's and feminists' demands ranging from a radical depatriarchalizing process to the more conventional acknowledgment of their rights in the legal systems. These questions present a fundamental challenge because there is neither one discourse of the Buen Vivir nor of feminism, but rather different meanings are attached to them. Rather than deepening into a genealogical or epistemological study of these theoretical and political proposals, this paper explores the contradictions within and between these in the framework of the Constitutional Assemblies in Bolivia and Ecuador. It concludes that, although Buen Vivir and decolonial feminist approaches can be complementary, the conceptualizations of Buen Vivir must not be a horizon that postpones women's aspirations indefinitely but a daily reality supported by explicit State policies and actions.
Keywords: 330